Evaluation of E-Performance CIPP Model on the Merdeka Mengajar Platform at SMPN 1 Maiwa - Darmawati Darmawati; Sahraini Sahraini; Kartini Kartini (Har Press Indonesia, 2024)
This study aims to evaluate the implementation of the E-Performance program on the Merdeka Mengajar Platform at SMPN 1 Maiwa using the CIPP (Context, Input, Process, Product) evaluation model. This research adopts a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The evaluation results for the context aspect indicate that the implementation of E-Performance is motivated by the need to improve the efficiency of teacher performance appraisal and to address weaknesses in psychological support and classroom management as shown by the education report card. Teachers and the principal demonstrate a clear understanding of the role of E-Performance in supporting data-driven learning, although student involvement remains limited. In the input aspect, it was found that teachers’ readiness to use E-Performance is uneven, training has not been systematic, and technical issues such as internet access continue to pose challenges. Additionally, internal regulations and external supervision are not yet fully optimized. The process aspect shows that the program is routinely carried out through the completion of RHK and reporting activities; however, it still faces operational technical difficulties and a lack of follow-up supervision focused on improvement. Meanwhile, in the product aspect, the E-Performance program positively impacts time efficiency, reporting consistency, and teachers’ reflective awareness. Nonetheless, the increase in motivation and innovation in learning is uneven, and the use of evaluation results for professional development remains limited. These findings highlight the need to strengthen training, internal regulations, infrastructure support, and ongoing monitoring strategies so that E-Performance can serve as an effective and sustainable tool for improving teacher performance.